The Concept of Human Capital: Categorical Analysis of the Evolution of Approaches - I. D. Turgel; D. Fazylzhan (Экономика: стратегия и практика, 2023)
The concept of human capital is being actualized in the conditions of global turbulence. Both classics of political economy and modern economic scientists have significantly contributed to the conceptualization of human capital over the centuries. In the period of global uncertainty and the transformation of economic relations, one can notice the lack of a specific approach to the concept. In the global economy, human capital plays a role that determines and reveals the true causes of various economic and social phenomena. Economists consider human capital as a category of economic science, which is at the origins of economic well-being and development. The purpose of this study is to explicate various approaches to the study of the concept of human capital that can have a significant impact on further research. The article reviews and attempts to categorize theoretical interpretations of the concept of human capital. When writing the article, the method of retrospective analysis of research on the concept of human capital was used to categorize various schools and directions. The analysis allowed us to identify four main categories of approaches in research on human capital. Based on this, the authors noted the need to introduce semantic additions to the concept, considering modern realities. Based on the results obtained, the authors attempted to conceptualize human capital in the latest conditions. The analysis carried out in the article showed that the study of the concept of human capital requires a modern interpretation, including all previous theoretical developments and new aspects related to the requirements of the time.